Structure and substrate specificity of the Pim-1 kinase. - Bullock, A; Debreczeni, J; Amos, A; Knapp, S; Turk, B (2005)
The Pim kinases are a family of three vertebrate protein serine/threonine kinases (Pim-1, -2, and -3) belonging to the CAMK (calmodulin-dependent protein kinase-related) group. Pim kinases are emerging as important mediators of cytokine signaling pathways in hematopoietic cells, and they contribute to the progression of certain leukemias and solid tumors. A number of cytoplasmic and nuclear proteins are phosphorylated by Pim kinases and may act as their effectors in normal physiology and in disease. Recent crystallographic studies of Pim-1 have identified unique structural features but have not provided insight into how the kinase recognizes its target substrates. Here, we have conducted peptide library screens to exhaustively determine the sequence specificity of active site-mediated phosphorylation by Pim-1 and Pim-3. We have identified the major site of Pim-1 autophosphorylation and find surprisingly that it maps to a novel site that diverges from its consensus phosphorylation motif. We have solved the crystal structure of Pim-1 bound to a high affinity peptide substrate in complexes with either the ATP analog AMP-PNP or the bisindolylmaleimide kinase inhibitor 2-[1-(3-dimethylaminopropyl)-1H-indol-3-yl]-3-(1H-indol-3-yl)maleimide HCl. These structures reveal an unanticipated mode of recognition for basic residues upstream of the phosphorylation site, distinct from that of other kinases with similar substrate specificity. The structures provide a rationale for the unusually high affinity of Pim kinases for peptide substrates and suggest a general mode for substrate binding to members of the CAMK group.